Comparative Study on EDM of Ti-6Al-4V Using Circular and Convex Shaped Electrodes - Rajamanickam, S; Palani, R; Sathyamoorthy, V; Jagadeesh Varma, Muppala; Shaik Mahammad Althaf, Shaik; Michel Thilak, Antony (International Journal of Engineering and Technology, 2018)
As on today, Electrical Discharge Machining (EDM) is world famous unconventional machining process for electrically conductive materials. In this project work, Ti-6Al-4V is performed in electrical discharge machining using differently shaped (circular and convex) copper electrode. The machining parameters considered are the pulse on- time, pulse off-time, voltage and current to investigate machining characteristics like material removal rate and tool wear rate. Taguchi method is applied to frame experimental design. Ti-6Al-4V finds wide usage in industrial applications such as marine, aerospace, bio-medical and so on.Â